2017
DOI: 10.1007/s00227-016-3059-8
|View full text |Cite
|
Sign up to set email alerts
|

Icelandic herring-eating killer whales feed at night

Abstract: Herring-eating killer whales debilitate herring with underwater tail slaps and likely herd herring into tighter schools using a feeding-specific low-frequency pulsed call (‘herding’ call). Feeding on herring may be dependent upon daylight, as the whales use their white underside to help herd herring; however, feeding at night has not been investigated. The production of feeding-specific sounds provides an opportunity to use passive acoustic monitoring to investigate feeding behaviour at different times of day.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…There, therefore, appears to be a shift in community structure at these lower trophic levels which have impacts up the food chain resulting in decreases in herring recruitment and abundance (Brosset et al, 2019). Herring are known to be a hugely important prey species for humpback whales in both the North Pacific and the North Atlantic (Gavrilchuk et al, 2014; Jourdain & Vongraven, 2017; Moran et al, 2018; Richard et al, 2017). In fact, forage fish, specifically capelin and herring together, are estimated to make up 44% of their diet in the GSL (Gavrilchuk et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There, therefore, appears to be a shift in community structure at these lower trophic levels which have impacts up the food chain resulting in decreases in herring recruitment and abundance (Brosset et al, 2019). Herring are known to be a hugely important prey species for humpback whales in both the North Pacific and the North Atlantic (Gavrilchuk et al, 2014; Jourdain & Vongraven, 2017; Moran et al, 2018; Richard et al, 2017). In fact, forage fish, specifically capelin and herring together, are estimated to make up 44% of their diet in the GSL (Gavrilchuk et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It was noticeably more common in Breiðafjörður, despite the overall larger sample of calls from Vestmannaeyjar. Recordings from Vestmannaeyjar were only collected during daytime, while the sample from Breiðafjörður included many hours of recordings collected at night with the EAR when herding calls occurred more frequently (Richard et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, the prevalence of I36 was mainly driven by its frequent occurrence in Breiðafjörður. Richard et al (2017) found that the herding call was recorded more often at night. A large proportion of the recordings from Breiðafjörður was collected in the winter months using an EAR and thus included many hours of night‐time recording, while recordings from Vestmannaeyjar were only collected during daytime and in summer.…”
Section: Discussionmentioning
confidence: 99%
“…Cetaceans use sound for communication, foraging, and to obtain information about their environment (Richardson et al, 1995), which allows many species to be detected through passive acoustic monitoring (PAM). Unlike visual survey methods, PAM facilitates long-term observation of cetaceans because it can operate in poor weather conditions, at night, and in study areas that are difficult to reach, while causing little interference in the subject's behavior (Au et al, 2013;Oswald et al, 2016;Richard et al, 2017;Sirovic ´et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While duty cycles are frequently used in long-term studies of cetaceans, the selection of cycle length or listening proportion is not consistent. For example, in passive acoustic studies of killer whales that use duty cycles, cycle lengths range from 5 to 240 min, and listening proportions from 0.1 to 0.67 (Hannay et al, 2013;Hanson et al, 2013;Rice et al, 2017;Richard et al, 2017;Riera et al, 2019). Additionally, in most published studies using duty-cycled data, the selection of the duty cycle is only justified based on the storage capacity and battery life of the recorder and not related to the acoustic behavior of the focal species (e.g., Diogou et al, 2019;Hanson et al, 2013;Lammers et al, 2017).…”
Section: Introductionmentioning
confidence: 99%